Radar Remote Sensing of Urban Areas - Soergel, Uwe. (Remote Sensing and Digital Image Processing, 2010)
This book presents a unique collection of state-of-the-art contributions by international remote sensing experts focussing on methodologies to extract information about urban areas from Synthetic Aperture Radar (SAR) data. SAR is an active remote sensing technique capable to gather data independently from sun light and weather conditions. Emphasizing technical and geometrical issues the potential and limits of SAR are addressed in focussed case studies, for example, the detection of buildings and roads, traffic monitoring, surface deformation monitoring, and urban change. These studies can be sorted into two groups: the mapping of the current urban state and the monitoring of change. The former covers, for instance, methodologies for the detection and reconstruction of individual buildings and road networks; the latter, for example, surface deformation monitoring and urban change. This includes also investigations related to the benefit of SAR Interferometry, which is useful to determine either digital elevation models and surface deformation or the radial velocity of objects (e.g. cars), and the Polarization of the signal that comprises valuable information about the type of soil and object geometry. Furthermore, the features of modern satellite and airborne sensor devices which provide high-spatial resolution of the urban scene are discussed. Audience: This book will be of interest to scientists and professionals in geodesy, geography, architecture, engineering and urban planning.